Correction: POPs in Antarctic ecosystems: is climate change affecting their temporal trends?. Issue 1 (20th December 2022) - Corsolini, Simonetta; Ademollo, Nicoletta
Abstract : Correction for 'POPs in Antarctic ecosystems: is climate change affecting their temporal trends?' by Simonetta Corsolini et al., Environ. Sci.: Processes Impacts, 2022, 24, 1631–1642, ; https://doi.org/10.1039/D2EM00273F .